Respuesta :

Answer:

3x-2y-6=0

Step-by-step explanation:

Gotta get y and x to the same side. Add 3 to both sides to get y+3=3/2x. Then, subtract -3/2x from both sides. Then you have -3/2x+y+3=0. Multiply by -2 to get x positive and by itself. You are left with 3x-2y-6=0

Answer:

c

Step-by-step explanation:

The general form is represented by Ax+By+C=0

In order to do this, we have to transfer the x value, y value, and the coefficient to one side.

Do this by subtracting [tex]\frac{3}{2}[/tex]x  and adding 3 on both sides so that the equation now reads [tex]-\frac{3}{2} + y + 3 =0[/tex]

General form cannot have fractions so then you would multiply everything by -2 to get rid of the fraction and negative. This will lead you to the answer